Chantal Akerman - Travelling - Brouwez, Céline; Ponsa, Marta; Rassel, Laurence; Sessa, Alberta (Bozar-Centre for Fine Arts, 2024)
"Filmmaker and artist Chantal Akerman was one of the most fearless filmmakers of her generation. Her work blurs the boundaries of time and space, of film and art. It can be seen in cinemas and museums worldwide. She may be largely unknown to the general public, but she is revered by cinephiles, visual artists and filmmakers.00The impact of her oeuvre on world cinema became abundantly clear when 'Jeanne Dielman, 23, quai du Commerce, 1080 Bruxelles' was named best film of all time by British magazine 'Sight and Sound'.00In 2024, Bozar-Centre for Fine Arts, Jeu de Paume and CINEMATEK will pay tribute to Akerman by organising the first major exhibition on the Brussels artist. This book accompanying the exhibition features people who were closest to Akerman and can offer unique insights: the people who worked with her or were inspired by her."
Impressum: This catalogue was published in conjunction with the exhibition "Chantal Akerman. Travelling": Bozar-Centre for Fine Arts, Brussels, 14 March - 21 July 2024; Jeu de Paume, Paris, 28 September 2024 - 19 January 2025
Keywords: Akerman, Chantal -- 1950-2015; Filmregisseurin; Ausstellungskatalog -- Palais des Beaux-Arts -- 14.03.2024-21.07.2024 -- Brüssel; Ausstellungskatalog -- Jeu de Paume -- 28.09.2024-19.01.2025 -- Paris